2011
DOI: 10.1038/emboj.2011.397
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic biology approach to reconstituting the ubiquitylation cascade in bacteria

Abstract: Covalent modification of proteins with ubiquitin (Ub) is widely implicated in the control of protein function and fate. Over 100 deubiquitylating enzymes rapidly reverse this modification, posing challenges to the biochemical and biophysical characterization of ubiquitylated proteins. We circumvented this limitation with a synthetic biology approach of reconstructing the entire eukaryotic Ub cascade in bacteria. Co-expression of affinity-tagged substrates and Ub with E1, E2 and E3 enzymes allows efficient puri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(83 citation statements)
references
References 69 publications
3
75
1
4
Order By: Relevance
“…Therefore, we proved that the MIU domain is not only involved directly in the trafficking of ubiquitinated cargo but also plays a key role in the coupled monoubiquitination of Rabex-5 to inactivate its ubiquitinated cargo-binding activity. However, our results differ from a previous study by Keren-Kaplan et al (42), which reported that ubiquitination occurs on the Vps9-GEF domain and that it does not affect the GEF activity in vitro. This could be attributed to the different types of UBDs present in human Rabex-5 and yeast Vps9 proteins.…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, we proved that the MIU domain is not only involved directly in the trafficking of ubiquitinated cargo but also plays a key role in the coupled monoubiquitination of Rabex-5 to inactivate its ubiquitinated cargo-binding activity. However, our results differ from a previous study by Keren-Kaplan et al (42), which reported that ubiquitination occurs on the Vps9-GEF domain and that it does not affect the GEF activity in vitro. This could be attributed to the different types of UBDs present in human Rabex-5 and yeast Vps9 proteins.…”
Section: Discussioncontrasting
confidence: 99%
“…There have also been advances in assays to assess proteasomal inhibition [11], FRET-based sensors to quantify single cell proteasome activity [12], and substrates to identify the importance of protein folding on proteasomal targeting and degradation kinetics [13]. Further, tools exist that can distinguish between different ubiquitin species (free, mono-, or polyubiquitin chains) in the cytosol [14] and perform biochemical and biophysical characterization of E3 ligase kinetics independent of DUBs in a synthetic ubiquitination cascade in bacteria [15]. Additionally, novel proteomics-based approaches have been developed using mass spectrometry and stable isotope labeling by amino acids in cell culture (SILAC) to perform high throughput identification of E3 ligase substrates [16], [17].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the inhibitor effects of DUBs, one group sought to reconstitute the E1-E2-E3 enzymatic cascade in bacteria (49). Co-expression of affinity-tagged substrates and ubiquitin resulted in purified proteins that were used to study E3 autoubiquitination and map ubiquitination sites on the E3 ligase Mindbomb.…”
Section: Measuring Ubiquitination Enzyme Activity and Polyubiquitin Cmentioning
confidence: 99%